Testing an Attachment-Based Parenting Intervention-VIPP-FC/A in Adoptive Families with Post-institutionalized Children: Do Maternal Sensitivity and Genetic Markers Count? - Barone, Lavinia; Barone, Virginia; Dellagiulia, Antonio; Lionetti, Francesca (Frontiers in Psychology, 2018)
This study investigated the effectiveness of a newly integrated version of an intervention targeting adoptive mothers' positive parenting for promoting children's emotional availability, by testing the moderating role of both two maternal genetic polymorphisms (i.e. 5HTTLPR and DRD4-VNTR ) and emotional availability-EA on intervention outcomes. Mothers with their children (N = 80; Mage = 42.73 years, SD = 3.79; Mage = 33,18 months, SD = 16.83 months) participated in a RCT testing the Video-Feedback Intervention to Promote Positive Parenting and Sensitive Discipline-VIPP-FC/A effectiveness. Mixed effects regression models showed a significant improvement in mother-child EA for the VIPP-intervention vs. the dummy intervention condition, with a moderating role of maternal EA on children's outcomes. No significant moderating effect was found for the two genetic polymorphisms inquired. Children's and mother's outcomes obtained are discussed.